A synopsis of the genus Crotalaria (Leguminosae) in Brazil - Flores, Andréia Silva; Tozzi, Ana Maria Goulart De Azevedo (Phytotaxa, 2018)
The genus Crotalaria (Leguminosae, Papilionoideae) comprises herbaceous and shrubby species with simple, 1–foliolate or 3 (4–5)–foliolate leaves, the stamens united in a sheath open at least at the base, with dimorphic anthers, and the legumes are inflated. This paper updates the taxonomy of Crotalaria in Brazil since the tratament of Bentham in Flora Brasiliensis. We provide a key, brief descriptions, illustrations and notes on affinities, geographical distribution and ecology for the 31 native and 11 introduced or naturalized species ocurring in Brazil. A lectotype for Crotalaria vespertilio Benth. is also designated.